The Effectiveness of Project-Based Learning Model with RAHMA Syntax to Improve Prospective Biology Teachers’ Critical Thinking Skills - Darussyamsu, Rahmawati; Lufri, Lufri; Ahda, Yuni; Alberida, Heffi; Ambiyar, Ambiyar; Samsudin, Syakirah (Universitas Negeri Semarang, 2024)
This research aims to measure the effectiveness of the Project-Based Learning Model with RAHMA Syntax (PjBL-RAHMA) in improving prospective biology teachers’ critical thinking skills. RAHMA is an acronym for Recognizing Problems, Analyzing Problems, Handling Projects, Monitoring Progress, and Assessing Results. This research was quasi-experimental with a posttest-only control group design. This research involved 223 prospective biology teachers from three well-accredited public universities in Sumatra, Indonesia. Data from the critical thinking skills test results were analyzed using JASP software. Prospective biology teachers’ achievement of critical thinking skills after learning using the PjBL-RAHMA model showed that the experimental class was better than the control class. This research concludes that PjBL-RAHMA effectively improves prospective biology teachers’ critical thinking skills. This research also explains the contribution of each PjBL-RAHMA syntax in improving prospective biology teachers’ critical thinking skills. The PjBL-RAHMA syntax has increased prospective biology teachers’ ability to understand and analyze real-life problems, providing good reasons, logical thinking, and creating solutions to problems, especially in pedagogy.